Effectiveness of nefopam-dexamethasone versus pethidine-dexamethasone for postoperative pain management in cesarean sections: a double-blind, prospective clinical trial - Julian Ojebo; Joseph Achi; Ifeanyichukwu Michael Chukwu; Osadebamen Mercy Oboh; Benedict Ezeife; Aisha Sanusi Muazu; Christian Osemudiamen Igibah; Salami Ezekiel Kelvin (Bali Journal of Anesthesiology)
Abstract Background: Postoperative pain management has been found to reduce postoperative morbidity, length of hospital stays, and overall healthcare cost and increased patient satisfaction. There is currently no gold standard for pain management in the immediate postoperative period following cesarean section. The goal of this study was to assess the effectiveness of nefopam for postoperative pain management in cesarean section compared with pethidine. Materials and Methods: A total of 144 ASA II and III pregnant women scheduled for cesarean section under spinal anesthesia were recruited in the study. The two groups of patients were randomly assigned, receiving either nefopam-dexamethasone (group N) or pethidine-dexamethasone (group P). The measured outcomes were pain scores measured by the numeric rating scale (NRS), time to first analgesic request, side effects. Results: The demographic properties of the patients were comparable. No patients reported moderate or worse pain. Patients in group N reported lower NRS scores compared with group P. However, the differences were not statistically significant. Moreover, the time to first analgesic request was 315.18 ± 103.61 min in group N and 286.86 ± 101.79 min in group P (P = 0.100). No side effects were noted in this study. Conclusion: The combination of nefopam and dexamethasone is equipotent to the combination of pethidine and dexamethasone in pain control after cesarean section and can be proposed as an alternative to opioids postoperatively.